1973
DOI: 10.3177/jnsv.19.23
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Serum Lipid Components and Serum Vitamin E in Iron Deficiency Anemia

Abstract: Investigations were carried out on serum lipid components and serum vitamin E in 54 cases of iron deficiency anemia during adolescence, with the following results: Serum levels of total lipids, free fatty acids, and phospholipids in cases of iron deficiency anemia were not different from those of the controls. Although the average value: of serum total cholesterol levels in the cases of iron deficiency anemia was not different from that of the controls, the percentage of subjects who showed low serum total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…However, Ece et al 9 in a study on IDA children reported reduced LDL levels, which returned to control levels after the iron therapy. Serum TC did not show any significant alteration in the IDA group while previous studies have reported variable results in relation to TC, with some studies reporting it as normal, 10,20 while others reporting low levels. 8,9 Various studies have been performed to define the related mechanisms underlying dyslipidemias in IDA.…”
contrasting
confidence: 65%
“…However, Ece et al 9 in a study on IDA children reported reduced LDL levels, which returned to control levels after the iron therapy. Serum TC did not show any significant alteration in the IDA group while previous studies have reported variable results in relation to TC, with some studies reporting it as normal, 10,20 while others reporting low levels. 8,9 Various studies have been performed to define the related mechanisms underlying dyslipidemias in IDA.…”
contrasting
confidence: 65%
“…Bloor and MacPherson (17) and Erickson et al (18) reported elevated lipids in anemic subjects. Others have found hypolipidemia in patients with anemias of various origins (19)(20)(21)(22) or no significant relationships between anemia and serum lipids (23). Since hyperlipidemia is recognized as a risk factor in the development of atherosclerotic heart disease, all nutritional influences on serum lipid concentrations assume considerable importance and warrant further study to enable us to more clearly understand the etiology of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, lower cholesterol levels were reported in anemic humans by Elwood et al (1) and Rifkind and Gale (3). But Fujii and Shimizu (2) found no significant difference in total cholesterol levels between subjects with hemoglobin (Hb) levels less than 10.9g/100ml and greater than 12.0g/100ml. These studies suggest that there is a certain critical level of Hb for cholesterol decrement.…”
mentioning
confidence: 96%
“…Effects of anemia on lipid levels in blood have been studied both in human (1)(2)(3)(4) and in animal (5)(6)(7)(8)(9)(10)(11)(12). The lipemia in iron-deficient and anemic animals is associated with elevated triglyceride levels while cholesterol levels may (9) or may not (7,11) be elevated.…”
mentioning
confidence: 99%